The Concept of an "Act of a Sexual Nature" in Criminal Law. Issue 5 (August 2021) - Corrêa Camargo, Beatriz; Renzikowski, Joachim
Abstract: All jurisdictions assume a concept of an act of a sexual nature by regulating sex crimes. Until the sex revolution and feminist movements for equality in sexual relations, criminal law was mostly concerned with specific types of sexual acts, particularly non-marital sexual intercourse. With the paradigm shift of recent years, criminalization tends to embrace all acts of a sexual nature with another person without her valid consent. Whether the law contains a definition of a sexual act or not, borderline cases show that neither merely objective criteria nor purely subjective elements can serve as basis for the description of the conduct under prohibition. Our Article tries to overcome this deficit in the criminal law theory. Sexual acts should not be understood through the metaphor of a "picture, " as German legal scholars believe, but with the metaphor of a script played out by an actor as sexual theorists put it.